2013
DOI: 10.1371/journal.pone.0079493
|View full text |Cite
|
Sign up to set email alerts
|

Using Effort to Measure Reward Value of Faces in Children with Autism

Abstract: According to one influential account, face processing atypicalities in autism reflect reduced reward value of faces, which results in limited attention to faces during development and a consequent failure to acquire face expertise. Surprisingly, however, there is a paucity of work directly investigating the reward value of faces for individuals with autism and the evidence for diminished face rewards in this population remains equivocal. In the current study, we measured how hard children with autism would wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 39 publications
4
38
0
1
Order By: Relevance
“…Unlike preferential looking measures, behavioural approach or instrumental choice tasks have been less consistent in indicating preference for social stimuli in neurotypical children [20][21][22][23]. In the present study, we replicated the findings by Ruta and colleagues [23] using an adapted version of the original task.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Unlike preferential looking measures, behavioural approach or instrumental choice tasks have been less consistent in indicating preference for social stimuli in neurotypical children [20][21][22][23]. In the present study, we replicated the findings by Ruta and colleagues [23] using an adapted version of the original task.…”
Section: Discussionsupporting
confidence: 83%
“…The second set of studies examining social reward responsivity in instrumental paradigms used effort as an index of social reward responsivity. In tasks of this type, participants exert different amounts of effort (made through complex or multiple button presses) to obtain a social or a nonsocial reward [19,20]. These tasks demonstrate that neurotypical adults carefully evaluate the level of effort required and available outcomes while making a choice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings also revealed higher scores in affective drive predicted higher scores on the SII-SF. This showed that the interest or tendency to be sensitive to others’ emotions relates to a greater sense of feeling towards others [166168]. Findings also showed higher scores in cognitive ability predicted higher scores on the SII-SF.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this phenomenon is the atypical development in social motivation in ASD (Chevallier et al, 2012). Some also argue that atypical development in social motivation in individuals with ASD is related to the atypical development of social reward processing (Bartz et al, 2011;Modi and Young, 2012;Dubey et al, 2015), although others did not find differences in the reinforcement value of social stimuli between individuals with and without ASD (e.g., Ewing et al, 2013;Vernetti et al, 2018). Overall, there is a theoretical and clinical interest in the possible influence of social motivation on the development of social attention and learning.…”
Section: Experiments 2: Modeling Individual Differencesmentioning
confidence: 99%